2009
DOI: 10.1007/s11738-009-0406-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and antioxidant responses of Mentha pulegium (Pennyroyal) to salt stress

Abstract: Mentha pulegium L. is a medicinal and aromatic plant belonging to the Labiatae family present in the humid to the arid bioclimatic regions of Tunisia. We studied the effect of different salt concentrations on plant growth, mineral composition and antioxidant responses. Physiological and biochemical parameters were assessed in the plant organs after 2 weeks of salt treatment with 25, 50, 75 and 100 mM NaCl. Results showed that, growth was reduced even by 25 mM, and salt effect was more pronounced in shoots (lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
78
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 34 publications
15
78
0
5
Order By: Relevance
“…Similar results were reported in Nigella sativa showing that the phenolic contents were also affected significantly due to salt stress [7]. Queslati et al [31] demonstrated the increase of phenols following saline treatment of Mentha pulegium. Salinity stress-induced total phenolic content accumulation has also been previously observed in strawberry and sugarcane [14].…”
Section: Discussionsupporting
confidence: 75%
“…Similar results were reported in Nigella sativa showing that the phenolic contents were also affected significantly due to salt stress [7]. Queslati et al [31] demonstrated the increase of phenols following saline treatment of Mentha pulegium. Salinity stress-induced total phenolic content accumulation has also been previously observed in strawberry and sugarcane [14].…”
Section: Discussionsupporting
confidence: 75%
“…Hence, the salt stimulating effect in Soliman could explain the maintenance of plant vigor up to 6 weeks of salt treatment. Our results are in agreement with those of Oueslati et al (2010) who found an increase in total polyphenols and antiradical activities in a different Tunisian provenance (Nefza) of the same species. Navaro et al (2006) also demonstrated that total phenolic concentration increased with salinity level in red pepper fruits.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with those of Oueslati et al (2010) who found that the whole plant dry weight of this species was reduced by 46, 59, and 58%, respecttively at 25, 50 and 75 mM NaCl. Nevertheless, intraspecific variability in salt-induced responses was revealed in our study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, Cik et al (2009) found that accumulation of phenolic acids (protocatechuic, chlorogenic and caffeic acids) on Matricaria chamomilla increased by salinity. Bourgou et al (2010) showed increase of phenols with saline treatment on Nigella sativa and Queslati et al (2010) on Mentha pulegium.…”
Section: Resultsmentioning
confidence: 98%